ABORTION IN ISLAMIC LAW AND ITS INTERSECTION WITH HUMAN RIGHTS - Rahajeng, Andini Naulina (Journal of Islamic Law Studies, 2020)
Abortion was legally restricted in almost every country by the end of the nineteenth century. Abortion is a controversial topic due to its involving with fundamental morals, ethics, and religious concerns. Legal restrictions on abortio n do exist throughout Islam jurisprudence, though allowed only with emergency circumstances. Nowadays, people become more aware of abortion as a part of human rights, as it is considered female autonomy over her body and part of reproductive rights. Abortion considered should be legally allowed and accessible to women. This paper will describe the construction of abortion in Islamic Law and the awareness of abortion as human rights.